Radio echo and magnetic sounding of the Antarctic ice sheet, 1978–79 - Drewry, D. J.; Meldrum, D. T.; Jankowski, E. (Polar Record, 1980)
During December 1978 the Scott Polar Research Institute (SPRI) undertook its sixth and final season of long-range airborne radio echo sounding (RES) and magnetometry in Antarctica in cooperation with the US National Science Foundation Division of Polar Programmes (NSF-DPP) and the Electromagnetics Institute of the Technical University of Denmark (TUD). The 1978–79 season (DF–79) was part of a long-term programme of glaciological and geophysical investigation of the Antarctic ice sheet (Drewry and Meldrum 1978a; 1978b). The broad aims have been to extend a 100-km grid network over Antarctica for a study of surface form, thickness, internal structure, rheology, thermodynamics, electrical properties, basal conditions and processes, and sub-ice geology.